Child maltreatment types and adolescent substance use: The role of deviant peer affiliation. Issue 2 (19th August 2019) - Yoon, Dalhee; Snyder, Susan M.; Yoon, Susan
Abstract: This is the first study to examine the mediating effects of deviant peer affiliation on the association between different types of child maltreatment and adolescent substance use that includes alcohol, tobacco, and marijuana. Peer deviance is a well‐established correlate of adolescent substance use, but most studies exploring the relationship between child maltreatment and adolescent substance use have failed to include peer deviance. Structural equation modelling was conducted to examine the direct effects of each type of child maltreatment (i.e., physical, sexual, and emotional abuse, and neglect) on adolescent substance use, as well as indirect effects via deviant peer affiliation, using Longitudinal Studies of Child Abuse and Neglect. The results indicated that deviant peer affiliation fully mediated the individuals who had been emotionally abused showed increased deviant peer affiliation, which in turn was associated with higher levels of adolescent substance use. None of the four types of child maltreatment was directly associated with adolescent substance use. The study's findings underscore the importance of early assessment and intervention for the peer relationships of youth who have been emotionally abused.